Coping with Globalization: Strategies to Promote Community Awareness and Engagement in Education - Jaya, Belardo Prasetya Mega; Luthfia, Chaula; Nida, Qotrun; Rayhan, Ahmad; Hanif, Hamdan Arief; Romdoni, Muhamad (Faculty of Law, Universitas Sultan Ageng Tirtayasa, 2024)
Efforts to improve access to and quality of education remain critical, yet gaps persist between theoretical initiatives and practical implementation, particularly in underdeveloped and marginalized regions. This study addresses the urgent need to enhance community awareness of education’s significance in navigating the challenges of globalization. Through community education and qualitative data collection, innovative strategies are introduced to engage local communities and promote active participation in educational activities. The approach emphasizes revitalizing educational awareness by identifying effective practices, implementing targeted interventions, and systematically evaluating their outcomes. These efforts aim to bridge the gap between awareness and action, fostering a culture of education that drives social and economic progress. By strengthening community involvement and improving the understanding of education’s transformative potential, this initiative contributes to sustainable development and positions education as a cornerstone for empowering future generations in an increasingly globalized world.